Somatic Energies and Emotional Traumas: A Qualitative Study of Practice-Related Challenges Reported by Vajrayāna Buddhists - Lindahl, Jared R. (Religions, 2017)
A qualitative study of Western practitioners of Buddhist meditation investigated unexpected, challenging, difficult, and distressing experiences. This paper reports on a subset of 12 practitioners within Tibetan Vajrayāna lineages who described energy flowing through their body, knots of pain, pressure or tension, and/or concurrent emotional changes. In some cases, somatic changes were appraised as practice-related transient states, and in other cases practitioners were given a Tibetan medical diagnosis of rlung disorder. Releases of tension in the body or subtle body also sometimes coincided with an upwelling of emotionally charged content. Practitioners reported emotional upwelling during subtle body practices as well as during other Vajrayāna practices, such as visualizations. While some practitioners viewed these experiences in relation to a normative Tantric soteriology of purification, almost all practitioners with a trauma history reported traumatic re-experiencing and tended not to adopt a purification framework. These practitioners were also more likely to seek additional psychotherapeutic or medical treatment to help resolve their practice-related challenges. The manner in which somatic and affective experiences manifest, how they are appraised, and how they affect the practitioner's ability to engage in the Vajrayāna path depends upon many individual, interpersonal, and cultural factors.